Experimental and Numerical Investigation of Heat Transfer Augmentation Using Al2o3-Ethylene Glycol Nanofluids Under Turbulent Flows in a Flat Tube - M. Kh., Abdolbaqi; Nor Azwadi, Che Sidik; Muhammad Noor Afiq Witri, Mohd Yazid; R., Mamat; Azmi, W. H.; Hind, M. Kh. (Penerbit Universiti Teknologi Malaysia, 2016)
A study of computational fluid dynamics has been conducted to study the characteristics of the heat transfer and friction factor of Al2O3/Ethylene glycol-water nanofluid flowing inside flat tube. The three dimensional realizable k?e turbulent model with an enhanced wall treatment was utilized. The evaluation of the overall performance of the tested tube was predicated on the thermo-hydrodynamic performance index. The obtained results showed that the difference in behaviour depending on the parameter that has been selected to compare the nanofluid with the base fluid. In addition, the friction factor and the heat transfer coefficient increases with an increase of the nanoparticles volume concentration at the same Reynolds number. The penalty of pressure drop is negligible with an increase of the volume concentration of nanoparticles. Conventional correlations that have been used in turbulent flow regime to predict average heat transfer and friction factor are Dittus-Boelter and Blasius correlations, for tubes are also valid for the tested nanofluids which consider that the nanofluids have a homogeneous fluid behaviour.